2012
DOI: 10.1155/2012/146396
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Bandgaps in 1D Arrays of Slits on Metal Layers Excited by Out-of-Plane Sources

Abstract: We analyze the effective opening of finite bands of inhibited transmission in realistic systems excited by actual out-of-plane sources. We first observe how the excitation of surface plasmon polaritons in one-dimensional arrays of metal slits depends on the angle of incidence of the source field. Then, the well-known grating-coupling equation is revised in order to find an asymmetric structure with equivalent parameters which, under perfectly normal excitation, is able to exhibit surface plasmon polariton mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In order for the electromagnetic field to obey the periodic conditions, the potential field on surfaces V1 , V2 , V3 , V4 must satisfy the boundary conditions (5) in the medium V = 1, 2 and 3. In regions distant from the source, the potential field must satisfy the limit boundary conditions (6).…”
Section: Electromagnetic Model Of Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…In order for the electromagnetic field to obey the periodic conditions, the potential field on surfaces V1 , V2 , V3 , V4 must satisfy the boundary conditions (5) in the medium V = 1, 2 and 3. In regions distant from the source, the potential field must satisfy the limit boundary conditions (6).…”
Section: Electromagnetic Model Of Sensormentioning
confidence: 99%
“…Recently, research has shown that, on particular conditions, SPP waves can be efficiently used to control the near field intensification in metal nanostructures [6,7]. The study of these phenomena has been of great importance for the development of SPR sensors devices for applications in biosensing, photodetection, spectroscopy, and detection of metallic nanopoluents resulting from nanofabrication processes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the nanogratings are called the continuous nanogratings with rectangular (or tapered) cross-section because they are placed on a thin layer of the same metal to fabricate the modified device structure. The linearly polarized incident radiation of light with appropriate frequency and angle of incident satisfies the dispersion relation equation; hence, the SPP diffraction occurs [28]. The coupling of incident electromagnetic wave to the SPs on the nanograting assisted MSM-PD structure surface is shown in Figure 2.…”
Section: Nanostructured Msm Photodetector Designmentioning
confidence: 99%